2019
DOI: 10.3847/1538-4357/ab43ca
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: Evidence for Enriched Accretion onto Satellite Galaxies in Dense Environments

Abstract: We investigate the environmental dependence of the local gas-phase metallicity in a sample of star-forming galaxies from the MaNGA survey. Satellite galaxies with stellar masses in the range ()  < < M M 9 log 10 * are found to be ∼0.05 dex higher in metallicity than centrals of similar stellar mass. Within the low-mass satellite population, we find that the interstellar medium (ISM) metallicity depends most strongly on the stellar mass of the galaxy that is central to the halo, though there is no obvious diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 102 publications
(153 reference statements)
3
16
0
Order By: Relevance
“…One of the key elements of their argument is indeed the presence of a clear metallicity offset between centrals and satellites having the same SFR. A similar conclusion was recently reached by Schaefer et al (2019b), who looked at the resolved mass gas-phase metallicity of satellite and central galaxies extracted from the MaNGA survey.…”
Section: Gas-phase Metallicitiessupporting
confidence: 81%
See 2 more Smart Citations
“…One of the key elements of their argument is indeed the presence of a clear metallicity offset between centrals and satellites having the same SFR. A similar conclusion was recently reached by Schaefer et al (2019b), who looked at the resolved mass gas-phase metallicity of satellite and central galaxies extracted from the MaNGA survey.…”
Section: Gas-phase Metallicitiessupporting
confidence: 81%
“…It is now well established that, even when still forming stars at rates typical of what is observed in the star-forming main sequence, satellite galaxies in groups show gas-phase metallicities significantly higher (∼0.1-0.2 dex) than central galaxies of the same stellar mass. This increase in metallicity of the ISM has been reported by studies based on both fibre spectroscopy (e.g., Pasquali, Gallazzi, & van den Bosch 2012;Peng & Maiolino 2014;Wu et al 2017) and IFS data (e.g., Lian et al 2019;Schaefer et al 2019b) and appears to become more and more prominent with decreasing galaxy stellar mass (see Figure 17). While these observational findings are overall in agreement with results from clusters of galaxies and generally interpreted as evidence for the cessation of infall of pristine gas and stripping of cold ISM from the outer disc (see Sections 4.2 and 4.4), for satellites in groups multiple scenarios have been proposed.…”
Section: Gas-phase Metallicitiessupporting
confidence: 77%
See 1 more Smart Citation
“…Balogh et al 2004;Poggianti et al 2006;Allen et al 2016;Owers et al 2019), a higher stellar metallicity (e.g. Schaefer et al 2019), older stellar ages (e.g. Thomas et al 2005;McDermid et al 2015), and a lower gas content (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The metallicity of galaxies in diverse environments is extensively studied in the local Universe. Small but significant environmental dependence of the MZR is found, especially for satellite galaxies, such that at a given stellar mass, galaxies in overdensities have higher gas-phase metallicities (e.g., Cooper et al 2008;Ellison et al 2009;Peng & Maiolino 2014;Wu et al 2017;Schaefer et al 2019). Cooper et al (2008) found that 15% of the measured scatter in the MZR is caused by environmental effects.…”
Section: Introductionmentioning
confidence: 99%